Implikasi Kebijakan Tenaga Kerja Asing terhadap Daya Saing dan Peluang Kerja Tenaga Kerja Domestik di Indonesia - Maya Widyastuti; Padrisan Jamba (IAIN Langsa, 2026)
This study aims to analyze the implications of foreign labor policies on industrial competitiveness and domestic labor opportunities, while identifying the legal and policy challenges arising from their implementation. The research employs a library-based (library research) qualitative approach, combining juridical-normative analysis with policy analysis, using primary sources such as laws, regulations, and government policy documents, and secondary sources including scholarly articles, books, and previous research reports. Findings indicate that while foreign labor can enhance productivity and facilitate technology transfer, without effective selection mechanisms and oversight, the policy may disadvantage domestic workers. The study emphasizes the necessity of an integrative policy framework that balances industrial competitiveness with the protection of domestic labor rights.